Komunikasi dalam Organisasi Pendidikan - Matondang, Aflah Husnaini; Nasution, Fadhilah Hilmy; Annisak, Fadillah; Parapat, Khoiriah Marta; Puspitasari, Putri (Pusdikra-Publishing.com, 2025)
Communication is a crucial aspect of organizational success, including in the educational sector. As the primary means of social interaction, communication facilitates coordination, information management, and the achievement of organizational goals. In educational organizations, communication serves several key functions: informative, regulatory, persuasive, and integrative. These functions enable management and employees to adapt, share information, and perform tasks effectively. This study employs a qualitative approach using a literature review method to explore and analyze the functions of communication in educational organizations. Organizational communication can be categorized into vertical, horizontal, and diagonal communication, each playing a specific role in sustaining organizational activities. In the context of education, communication is vital for cultural transmission, adaptation, and institutional management. Without effective communication, educational organizations cannot achieve their objectives.